Lógica Fuzzy e Geoprocessamento na Determinação da Vulnerabilidade à Ocupação Direta dos Mangues na Bacia Hidrográfica do Anil na Ilha de São Luis - MA - Coelho, Cristiano Jackson da Costa (2008)
Mangroves are tropical ecosystems that thrive in intertidal areas known for their ecological importance. The loss of surface urbans Brazilian mangroves in areas that are located in estuaries is driven by a multitude of economic and social causes. The state of Maranhao, alone, has more than 500,000 hectares of mangrove forest (30% of all Brazilian mangroves) and Sao Luis, the capital, it possesses about 18,000 ago.